Analysis of genotype–phenotype correlation in patients with α‐thalassemia from Fujian province, Southeastern China. Issue 10 (13th September 2022) - Pan, Yali; Chen, Meihuan; Zhang, YanHong; Zhang, Min; Chen, Lingji; Lin, Na; Xu, Liangpu; Huang, Hailong
Abstract: Background: There is a high carrying rate of α‐thalassemia in Fujian province. However, there are few large‐scale studies on the correlation between genotype and phenotype in Fujian province. The purpose of this study was to analyze the phenotype and genotype in a cohort of 2923 patients with α‐thalassemia in Fujian province, so as to provide reference data for screening and diagnosis of α‐thalassemia in Fujian province. Methods: The genotype of α‐thalassemia was detected by PCR reverse dot blot assay, gap‐PCR, single PCR, nested PCR, and sequencing. Clinical and hematological indices of 2923 patients were collected, and the correlation between genotype and phenotype was analyzed. Results: Among 10, 350 patients, 2923 cases were found with α‐thalassemia, with a detection rate of 28.24%. Among them, ‐‐ SEA /αα was the most common genotype, accounting for 64.80%. In addition, rare α‐thalassemia genotypes were detected in Fujian province, including ‐‐ THAI /αα (0.41%), HKαα/‐‐ SEA (0.03%), and the novel α‐thalassemia gene mutation CD5 (GCC>ACC) (HGVS named HBA1: c.16G>A) (0.03%). Patients with deletional genotypes of α‐thalassemia were found to have higher RBC and lower Hb, MCV, MCH, and HbA2 than patients with non‐deletional genotypes of α‐thalassemia ( p < 0.05). Conclusion: The clinical phenotype of α‐thalassemia is influenced by molecular mechanisms. HBA1: c.16G>A mutation is a novel mutation that was first reported in Fujian province, which enriches the human hemoglobin mutation spectrum. Abstract : There were double peaks at nt224, G>A, in HBA1, corresponding to CD5 (GCC>ACC). It was named HBA1: c.16G>A using the Human Genome Variation Society (HGVS) nomenclature. HBA1: c.16G>A is a novel mutation that was first reported in Fujian province. The discovery of this novel mutation in α‐globin gene has enriched the database of hemoglobin variants, and the detailed genetic analysis and clinical symptom description of this mutation will contribute to the further study of hemoglobin function in the future.